ENVIRONMENTAL PERFORMANCE AND CSR DISCLOSURE ON FIRM VALUE THROUGH FINANCIAL PERFORMANCE - Edriani, Devi; Sari, Yosi Puspita; Yeni, Fitri (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2024)
This ponder points to analyze the affect of natural and corporate social obligation (CSR) as an interrelated variable of mechanical companies on corporate esteem through budgetary execution within the period 2017-2023. This investigation may be a quantitative inquire about covering 205 companies and could be a sampling strategy that points to test 22 companies. The comes about of this think about appear that natural execution contains a positive impact on monetary execution, whereas CSR divulgences have no impact on budgetary execution. Furthermore, natural execution has no impact on firm esteem, but CSR divulgence and money related execution have a positive and noteworthy impact on firm esteem. Subsequently, money related execution plays a part in intervening the relationship between natural execution and money related execution. In any case, monetary execution does not intervene the relationship between CSR and esteem acknowledgment.